Identification of novel interactors and potential phosphorylation substrates of GsSnRK1 from wild soybean (Glycine soja). (23rd May 2018) - Song, Yu; Zhang, Hang; You, Hongguang; Liu, Yuanming; Chen, Chao; Feng, Xu; Yu, Xingyu; Wu, Shengyang; Wang, Libo; Zhong, Shihua; Li, Qiang; Zhu, Yanming; et al.
Abstract: The plant sucrose nonfermenting kinase 1 (SnRK1) kinases play the central roles in the processes of energy balance, hormone perception, stress resistance, metabolism, growth, and development. However, the functions of these kinases are still elusive. In this study, we used GsSnRK1 of wild soybean as bait to perform library‐scale screens by the means of yeast two‐hybrid to identify its interacting proteins. The putative interactions were verified by yeast retransformation and β‐galactosidase assays, and the selected interactions were further confirmed in planta by bimolecular fluorescence complementation and biochemical Co‐IP assays. Protein phosphorylation analyses were carried out by phos‐tag assay and anti‐phospho‐(Ser/Thr) substrate antibodies. Finally, we obtained 24 GsSnRK1 interactors and several putative substrates that can be categorized into SnRK1 regulatory β subunit, protein modification, biotic and abiotic stress‐related, hormone perception and signalling, gene expression regulation, water and nitrogen transport, metabolism, and unknown proteins. Intriguingly, we first discovered that GsSnRK1 interacted with and phosphorylated the components of soybean nodulation and symbiotic nitrogen fixation. The interactions and potential functions of GsSnRK1 and its associated proteins were extensively discussed and analysed. This work provides plausible clues to elucidate the novel functions of SnRK1 in response to variable environmental, metabolic, and physiological requirements. Abstract : To reveal the functions of GsSnRK1 kinase of wild soybean, we used it as bait to screen cDNA library of wild soybean by employing yeast two‐hybrid technique. The result showed that GsSnRK1 interacted with 24 proteins that can be classified into several categories with different functions. These data will expand our views to understand the functions of SnRK1 kinases and provide more clues for us to dissect their regulating mechanisms.